SCREENING OF ASPERGILLUS FUNGI FOR EXTRA CELLULAR PROTEASE AND COLLAGENASE PRODUCTION - Blieva Raushan Kazhkenovna; Kalieva Aigul Kokomanovna; Suleimenova Zhanara Begezhanovna; Zhakipbekova Aigerim Sovetbekovna; Tapenbayeva Inkar Erkinbekkizi (Academic Journal of Physical and Chemical Sciences, 2020)
Protease and collagenase are the most important enzymes used for the processing of meat raw materials. In the meat industry, proteolytic enzymes are used to accelerate the maturation of meat and increase its yield. The use of enzyme preparations in meat processing makes it possible to rationally use meat raw materials, intensify technological processes, improve quality and expand the range of products. Collagenase, unlike protease, acts on those connective proteins of meat raw materials that determine its stiffness, breaking down hard-hydrolyzable and non-digestible collagen. The aim of this study was selection of strains of industrially valuable micromycetes from the collection of micromycetes that have the ability to synthesize extracellular protease and collagenase and create a fungal association. A comparative characterization of 7 strains of micromycetes of the genus Aspergillus and Penicillium - potential producers of protease and collagenase enzymes, was carried out. A. awamori 16 and A. awamori 22 showed the highest clearance zones and was used for further studies. The clearance zones of casein of A. awamori 16 on day 5 were 22.8 mm, and collagen 20.8 mm, while the clearance zones of casein of A. awamori 22 were 20.1 mm, and collagen - 19.1 mm.